استفادة مساعد جوجل (Google Assistent) في تعلم مهارة الكلام في القرن الحادي والعشرين - Nurlatipah, Nurlatipah; Rasyidah, Nafiatur; Uqba, M. Salih Solimul; Nuzula, M. Firdaus (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
This research is a type of qualitative descriptive research. The purpose of this research is to describe: (1) the utilization of Google Assistant-based technology in learning Maharah Kalam; (2) how Google Assistant provides feedback to train speaking skills. The problem in this study is the procedure of using Google Assistant in practicing speaking skills is very rarely known and applied by Arabic language learners. The method used in this research is literature study. Data collection techniques were carried out by means of intensive observation online on Google Assistant and documentation. Based on the analysis of the data obtained, two things were found: (1) Google Assistant is able to provide feedback to learners in practicing Maharah Kalam; (2) the utilization of Google Assistant in learning Maharah Kalam can be utilized in the world of education in a way, namely making it a learning medium in speaking skills directly so that it can be concluded that Google Assistant can be adopted by educators for learning Maharah Kalam as an effort to utilize technology. هذا البحث هو نوع من البحث الوصفي النوعي. الهدف من هذا البحث هو وصف: (1) استفادة التكنولوجيا المعتمدة على مساعد جوجل في تعلم مهارة الكلام؛ (2) كيف يقدم مساعد جوجل ملاحظات لممارسة مهارة التحدث. تكون المشكلة في هذا البحث أن إجراءات استخدام مساعد جوجل في ممارسة مهارة التحدث نادرة ما تكون معروفة ومطبقة من قبل متعلمي اللغة العربية. الطريقة المستخدمة في هذا البحث هي دراسة المراجع. تم تنفيذ تقنيات جمع البيانات من خلال المراقبة المكثفة عبر الإنترنت باستخدام مساعد جوجل والوثائق. وبناءً على تحليل البيانات التي تم البحث على أمرين: (1) مساعد  جوجل قادر على تقديم الملاحظات للطلاب في تدريب مهارة الكلام؛ (2) يمكن الاستفادة من استخدام مساعد جوجل في تعلم مهارة الكلام في تعليم اللغة من خلال جعله وسيلة تعليمية لمهارة التحدث مباشرة بحيث يمكن الاستنتاج أن مساعد جوجل  يمكن اعتماده من قبل معلمين اللغة في تعلم مهارة الكلام باعتباره وسيلة تعليمية للاستفادة من التكنولوجيا